Enhancing Family Support to Combat Treatment Non-Adherence in Multi-Drug Resistant Tuberculosis Patients at H. Adam Malik Hospital, Medan - Pane, Cindy Suci Veronika; Mutiara, Erna; Siregar, Fazidah Aguslina (Formosa Journal of Applied Sciences, 2024)
This study aims to analyze the impact of family support on treatment non-adherence in MDR-TB patients at H. Adam Malik Central General Hospital, Medan, in 2021. The research utilized a case-control design, with the study population comprising all outpatient MDR-TB patients who were adherent and non-adherent to treatment at H. Adam Malik Central General Hospital in 2022. The sample size included 51 adherent and 51 non-adherent patients. Data were analyzed using logistic regression. The results showed that family support significantly influenced treatment non-adherence in MDR-TB patients (OR=16,640; 95% CI 4,584-60,399; p=0.001). Integrating family support into the care of MDR-TB patients is recognized as an effective strategy to enhance adherence and treatment outcomes. Collaboration between medical teams and families can provide a foundation for a holistic MDR-TB treatment program.